Teachers’ Beliefs and Practice of Interaction Strategies on Students’ Willingness to Communicate - Jaenal Abidin; Mansyur Srisudarso; Putri Kamalia Hakim (Universitas Muhammadiyah Enrekang, 2021)
Willingness to Communicate (WTC) has become an important concept in second language (L2) classroom context. WTC is proven as a predictor of classroom participation since students who tend to have high WTC participated more in classroom interaction and they are likely to be ready to get involved in any interactions using their L2 both inside and outside classroom. Given the central role teachers play in pedagogy, who shape the curriculum within the context and content, and shape the decisions of teaching methods and strategy play dynamic role in maintaining students’ willingness to communicate. This study aims: (1) to portray teachers’ beliefs about their role and practice of interaction strategies in maintaining students’ WTC; (2) to find out interaction strategies employed by the teacher in maintaining students’ WTC. Employing narrative inquiry, the two experience English teacher was gathered by means of personal narrative and interview. The findings revealed that teacher plays a very crucial role in students’ WTC. This study also highlight that the use of three interaction strategies such as teacher-front, facilitator-oriented, and learner-oriented strategy can contribute in maintaining students’ WTC, by applying appropriate techniques. This study suggest that teacher should perform various roles to become an ideal guide in shaping students’ WTC. The use of various effective strategies with involving familiar term of topic, and the use of encouragement can be applied in encouraging English interaction. This present study is expected to create awareness on the significance of EFL teachers to share their interaction skills and vary effective interaction strategies improve the quality of English teaching and learning.